Simbolisme Agama dalam Politik Islam - Rochman, Ibnu (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2003)
The study of the symbolism of religion in Islamic politic is necessary to conduct because it is vast opportunity avaliable in the reformation and democratization era for most of Indonesian representing Moslem to express thier insight and thought that various forms ranging from vulgar, the emotion and the rational one. There are among the expression using symbols, even many Moslem who are active in practical politics Islamic symbols.Considering the title of the study